The Effect of the Project Based Learning Learning Model on the Ability of Problem Solving of Students at SMA Negeri 6 Kepahiang - Astria, Ririn; Haji, Saleh; Sumardi, Hari (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
This study aims to determine the effect of the Project Based Learning (PJBL) Learning Model on Students' Problem Solving Ability. This type of research uses the Quasi Experiment method. Data collection is done through tests. Data analysis used the Ancova test. The sample of this study were students of SMA Negeri 6 Kepahiang class XI IPA 1 and XI IPA 2. The results showed that: (1) There was a linear covariate effect of initial ability on students' problem solving abilities with an effect of 24.2%. (2) There is an influence of the Project Based Learning (PJBL) learning model on problem solving abilities of 76.2%. (3) There is a higher problem-solving ability achievement for class XI IPA students of SMA Negeri 6 Kepahiang who are taught using the Project Based Learning (PJBL) learning model compared to classes taught by conventional learning models.